Comparing the learning outcomes of lecture and self-instruction methods in a senior clinical laboratory science course - Zitzmann, M B (Clinical laboratory science, 1996)
To compare the relative effectiveness of lecture and self-instruction methods of instruction in a senior clinical laboratory science course. Posttest repeated measures design or within subject design. The Department of Medical Technology in the School of Allied Health Professions, Louisiana State University Medical Center, New Orleans. Clinical laboratory science students (27) enrolled in clinical parasitology agreed to participate, which was a sample of convenience. There were 16 females and 11 males; 70% Caucasian, 23% Asian, and 7% African-American. The 2 students who did not sign a consent form were excluded from the study. Subjects were taught clinical parasitology course material by 2 different methods of instruction, lecture and self-instruction. All subjects received both treatments. Examination scores from each half of the course were compared using descriptive statistics and a paired t-test to determine the effectiveness of each instructional format. Results showed no statistically significant difference in learning outcomes between the 2 instructional formats (a = 0.05, p = 0.13). The results of the study generally support the hypothesis that the self-instruction method is as effective as the lecture method in teaching clinical parasitology. By incorporating self-instruction into a clinical laboratory science curriculum, many hours of lecture can be eliminated, and students can learn the material at their own pace. Students comprehend the material effectively, and are relieved from some of the intensity of the didactic approach to instruction that dominates clinical laboratory science curricula.